Penguatan Karakter Islami Siswa MI Ma’arif Al Maksum melalui Implementasi Pesantren Ramadhan Kolaboratif - Chusna, Cahya Amalia; Putri, Tsania Aulia (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the implementation of experiential-based Islamic character education in Madrasah Ibtidaiyah (MI), despite its strategic role in shaping students’ moral and spiritual values, particularly in the digital era. The primary aim of this study is to describe the implementation of the Collaborative Ramadan Pesantren program as a strategy to strengthen Islamic character, analyze the internalization process of the values of honesty, responsibility, and social awareness, and identify behavioral changes among students after participating in the program. A descriptive qualitative method was employed using a Participatory Action Research (PAR) approach, involving 60 fourth- to sixth-grade students of MI Ma’arif Al Ma’shum Blora and 8 PGMI students from IAIKU Blora, selected through purposive sampling. Data were collected through participatory observation, informal interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings show that character reinforcement was carried out in three stages: collaborative planning, a three-day thematic activity based on direct experience, and evaluation and reflection aimed at fostering positive behavioral change. These results affirm the effectiveness of experiential and contextual character education. In conclusion, the collaborative and applicative approach proved effective in instilling Islamic values in elementary school students. The implications of this study include theoretical contributions to the development of Islamic character education and practical recommendations for madrasahs and higher education institutions in designing more structured and sustainable programs.